Insomnia Tendency among Adolescent Smartphone Users: Gender Difference and Prevalence - Fitriana, Anggun; Prabowo, Hendro (Jurnal Ilmiah Global Education, 2024)
The majority of Indonesian adolescents are smartphone users. Excessive use of smartphones, especially at night, can cause sleep difficulties known as insomnia. The study aims to determine gender difference and prevalence of insomnia tendency, pre-sleep activities, sleep duration, and difficulty sleeping among adolescent smartphone users. The cross-sectional design was used, involved 307 adolescents aged 13–18 years in Jabodetabek, Indonesia. Measures included an ISI questionnaire and information on gender, pre-sleep activities, sleep duration, and difficulty sleeping experience. Results showed that there is a significant difference (p 0,029) in insomnia tendency based on gender (female>male). Insomnia tendency is generally in the mild category with the prevalence of insomnia tendency 22,15% (moderate & severe). Respondents spent an average of 1 hour 22 minutes on the bed, using the internet via smartphone before asleep. Their sleep duration averaged 6,67 hours per night, 72% sleep less than 8 hours, and 51% feel don't get enough sleep. Furthermore, 58% reported difficulty sleeping, 24,43% experienced sleeping difficulties at least three nights per week, and 26,71% experienced sleeping difficulties for at least three months. Insomnia tendency is also generally found to increases with increasing frequency and duration of difficulty sleeping. These findings suggest that the insomnia tendency among adolescent smartphone users in Jabodetabek, Indonesia is high, especially compared with other countries. Therefore, it needs special attention from both academics and practitioners.